A New Perspective on Plasmonics: Confinement and Propagation Length of Surface Plasmons for Different Materials and Geometries. Issue 1 (21st September 2015) - Dastmalchi, Babak; Tassin, Philippe; Koschny, Thomas; Soukoulis, Costas M.
Abstract : Surface‐plasmon polaritons are electromagnetic waves propagating on the surface of a metal. Thanks to subwavelength confinement, they can concentrate optical energy on the micrometer or even nanometer scale, enabling new applications in bio‐sensing, optical interconnects, and nonlinear optics, where small footprint and strong field concentration are essential. The major obstacle in developing plasmonic applications is dissipative loss, which limits the propagation length of surface plasmons and broadens the bandwidth of surface‐plasmon resonances. Here, a new analysis of plasmonic materials and geometries is presented which fully considers the tradeoff between propagation length and degree of confinement. It is based on a two‐dimensional analysis of two independent figures of merit and the analysis is applied to relevant plasmonic materials, e.g., noble metals, aluminum, silicon carbide, doped semiconductors, graphene, etc. The analysis provides guidance on how to improve the performance of any particular plasmonic application and substantially eases the selection of the plasmonic material. Abstract : Designing plasmonic applications demands a proper understanding of plasmonic materials and geometries. A coherent method is developed to evaluate the performance of plasmonic materials by representing the propagation length, the degree of confinement, and the operational frequency range in a single graph. A comprehensive overview and comparison of common and cutting‐edge plasmonic materials and geometries is presented using this universal framework.